Bioacumulación de cadmio y plomo en Arundo donax L., Cyperus alternifolius y Leonotis nepetifolia en sedimentos aluviales en Samne, La Libertad – Perú - ESCOBAR CACHI, Genesis Elizabeth (2019)
The present study aimed to determine the bioaccumulation of cadmium and lead in root, stem and leaves of Arundo donax L., Cyperus alternifolius L. and Leonotis nepetifolia (L.) R. Br. In alluvial sediments in Samne, La Libertad - Peru. The three species mentioned above were evaluated, performing six samples per specie over a period of three months. The bioaccumulation of cadmium and lead was determined by the method of atomic absorption spectrophotometry, which was found as maximum values for cadmium at root level 1.69323 ppm in Cyperus alternifolius L., stem level 1.30367 ppm in Arundo donax L., at leaf level 0.8163 ppm in Leonotis nepetifolia (L.) R. Br., slightly exceeding the maximum permissible limits of the EPA and FAO; Likewise, for lead, the maximum bioaccumulation at the root and stem level was 6.52217 ppm and 3.94083 ppm, respectively, in Arundo donax L., and at the leaf level it was 2.80517 ppm in Leonotis nepetifolia (L.) R. Br., also slightly exceeding the maximum permissible limits of the EPA and FAO. We conclude that the study area may be in imminent danger due to the high contamination by heavy metals at the sediment level, as would the middle basin of the Moche river – Samne.